ANALYZING HUMOR IN TRANSLATION STRATEGIES AND TECHNIQUES IN THE AMAZING WORLD OF GUMBALL: THE BOSS - Hajuningdyah, Diaz Aninda (Journal of Language and Literature, 2024)
The research titled "Analyzing Humor in Translation Strategies and Techniques in The Amazing World of Gumball: The Boss" aims to analyze the translation strategies, techniques, and types of humor used by the translator in translating the subtitles of the animated television series. The study focuses on three main research questions: the translation strategies and techniques employed by the translator, and the type of humor used in these strategies and techniques. The research data consists of series subtitles translated from English into Indonesian. A descriptive qualitative research approach was employed, analyzing textual data rather than numerical data. The analysis was based on Gottlieb's (1998) ten subtitling strategies theory, Molina and Albir's (2002) theory of eighteen translation techniques, and Raphaelson-West's (1989) framework categorizing humor into linguistic, cultural, and universal humor types. The findings indicate that all ten subtitling strategies were applied, with the transfer strategy being the most frequently used. Sixteen out of eighteen translation techniques were employed, with literal translation being the most utilized. The translator utilized linguistic, cultural, and universal humor in the translation strategies and techniques. In conclusion, this research provides a comprehensive analysis of the translation strategies, techniques, and humor employed in the subtitles of the animated "The Amazing World of Gumball: The Boss". The study sheds light on the translator's approach and the impact on the audience's experience.